ANALISIS PERBANDINGAN KINERJA KEUANGAN DENGAN RISK BASED BANK RANKING PADA PT. BANK UOB INDONESIA SEBELUM DAN SESUDAH MELAKUKAN MERGER - Tsary Aristawati; Dwi Iga Luhsasi; Carolina Lita Permatasari (ITB AAS INDONESIA, 2022)
This study aimed to find out the difference of financial performance of banking companies whether they exist or not before and after the merger of PT Bank UOB Indonesia using risk approach (Risk-based Bank Rating). The data used in this study are secondary data obtained from the published annual financial reports of PT Bank UOB Indonesia. This research was conducted at PT Bank UOB Indonesia for a period of 3 years before the merger (2008-2010) and 3 years after the merger (2011-2013). The variables in this study consisted of 6 financial ratios, namely Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG), Return on Assets (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR). The data analysis technique has been done by using paired sample t-tests using the SPSS 20.0 program. Based on the result of the analysis, there were 3 financial ratios which do not have any significant difference i.e.: LDR, GCG, and ROA. Moreover, there are 3 financial ratios which have significant differences i.e.: NPL, NIM, and CAR which shows that the financial performance of the company undergoes significant changes before and after the merger.